2018
DOI: 10.1038/s41467-017-02618-6
|View full text |Cite
|
Sign up to set email alerts
|

Peptidomimetic blockade of MYB in acute myeloid leukemia

Abstract: Aberrant gene expression is a hallmark of acute leukemias. MYB-driven transcriptional coactivation with CREB-binding protein (CBP)/P300 is required for acute lymphoblastic and myeloid leukemias, including refractory MLL-rearranged leukemias. Using structure-guided molecular design, we developed a peptidomimetic inhibitor MYBMIM that interferes with the assembly of the molecular MYB:CBP/P300 complex and rapidly accumulates in the nuclei of AML cells. Treatment of AML cells with MYBMIM led to the dissociation of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
90
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 74 publications
(98 citation statements)
references
References 63 publications
(78 reference statements)
6
90
0
Order By: Relevance
“…Importantly, CRYBMIM achieved significantly improved, logarithmic suppression of growth and survival of most AML cell lines tested, as compared to MYBMIM and CREBMIM ( Figure 2F). For example, whereas MYBMIM induced nearly 100-fold suppression of growth of MV411 cells after six days of treatment in agreement with prior studies (Ramaswamy et al, 2018), CRYBMIM achieved more than 1,000-fold suppression compared to control (p = 8.6e-3; Figure 2F), consistent with its improved biochemical affinity ( Figure 1D). This improved activity of CRYBMIM spanned diverse MLL-rearranged and non-MLL-rearranged AML subtypes, AML1-ETO translocated, PML-RARA-translocated, DNMT3A-mutant, NPM1c-mutant, TP53-mutant, MYCamplified, and WT1-mutant cell lines, with the exception of erythroblastic BCR-ABL1-translocated K562 cells (10 of 11 cell lines tested; Figure 2F and Table S2).…”
Section: Potent and Broad-spectrum Activity Of Crybmim Against Diverssupporting
confidence: 90%
See 4 more Smart Citations
“…Importantly, CRYBMIM achieved significantly improved, logarithmic suppression of growth and survival of most AML cell lines tested, as compared to MYBMIM and CREBMIM ( Figure 2F). For example, whereas MYBMIM induced nearly 100-fold suppression of growth of MV411 cells after six days of treatment in agreement with prior studies (Ramaswamy et al, 2018), CRYBMIM achieved more than 1,000-fold suppression compared to control (p = 8.6e-3; Figure 2F), consistent with its improved biochemical affinity ( Figure 1D). This improved activity of CRYBMIM spanned diverse MLL-rearranged and non-MLL-rearranged AML subtypes, AML1-ETO translocated, PML-RARA-translocated, DNMT3A-mutant, NPM1c-mutant, TP53-mutant, MYCamplified, and WT1-mutant cell lines, with the exception of erythroblastic BCR-ABL1-translocated K562 cells (10 of 11 cell lines tested; Figure 2F and Table S2).…”
Section: Potent and Broad-spectrum Activity Of Crybmim Against Diverssupporting
confidence: 90%
“…Previously, we observed that MYBMIM blocks the binding of MYB to the CBP/P300 in AML cells, requiring relatively high 20 µM concentrations for 3 hours to achieve this effect (Ramaswamy et al, 2018). To ascertain whether CRYBMIM can achieve more potent interference with the binding of MYB to the CBP/P300 complex in cells due to its improved affinity as compared to MYBMIM ( Figure 1D), we treated MV411 cells with 10 µM peptides for one hour and immunoprecipitated CBP/P300 using specific antibodies ( Figure 2B).…”
Section: Potent and Broad-spectrum Activity Of Crybmim Against Diversmentioning
confidence: 94%
See 3 more Smart Citations